2015
DOI: 10.17219/acem/23362
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in Pain Perception in Adult Rats Lesioned as Neonates with 5.7-Dihydroxytryptamine

Abstract: The present study provides evidence that (1) an intact serotoninergic system is required for the adequate antinociceptive action of tramadol, and (2) the serotoninergic system exerts a negligible influence on acetaminophen-induced analgesia in rats. We hypothesize that similar abnormalities in nociception may occur in patients with 5-HT dysfunction (e.g. depression), so these results should be complied in analgesic dosage adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Second, the different targets contained in the PAG shown here to be involved in the analgesic effect of paracetamol (CB 1 and mGlu 5 receptors, TRPV1 channels) induced an analgesic effect when directly activated in the PAG, this effect being exerted through the activation of the bulbospinal pathways (de Novellis et al, ; Maione et al, , ; Palazzo et al, ; Starowicz et al, ). Additionally, injury to these pathways and particularly to the pathways using 5‐HT, reduced the analgesic effect of paracetamol in animals (Dogrul et al, ; Muchacki et al, ; Pini et al, ; Tjolsen et al, ), and their involvement in the analgesic effect of paracetamol has been demonstrated in humans (Pickering et al, ). Finally, a spinal involvement (suspected to be indirect) in the analgesic effect of paracetamol has been shown in animals: paracetamol reduces c‐Fos labelling in the dorsal horn of the spinal cord in animal models of inflammatory pain (Abbadie & Besson, ; Honoré et al, ), and its analgesic effect is reduced by the inhibition of different spinal 5‐HT receptors (Alloui et al, ; Bonnefont et al, ; Courade, Chassaing, Bardin, Alloui, & Eschalier, , Courade, Caussade, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the different targets contained in the PAG shown here to be involved in the analgesic effect of paracetamol (CB 1 and mGlu 5 receptors, TRPV1 channels) induced an analgesic effect when directly activated in the PAG, this effect being exerted through the activation of the bulbospinal pathways (de Novellis et al, ; Maione et al, , ; Palazzo et al, ; Starowicz et al, ). Additionally, injury to these pathways and particularly to the pathways using 5‐HT, reduced the analgesic effect of paracetamol in animals (Dogrul et al, ; Muchacki et al, ; Pini et al, ; Tjolsen et al, ), and their involvement in the analgesic effect of paracetamol has been demonstrated in humans (Pickering et al, ). Finally, a spinal involvement (suspected to be indirect) in the analgesic effect of paracetamol has been shown in animals: paracetamol reduces c‐Fos labelling in the dorsal horn of the spinal cord in animal models of inflammatory pain (Abbadie & Besson, ; Honoré et al, ), and its analgesic effect is reduced by the inhibition of different spinal 5‐HT receptors (Alloui et al, ; Bonnefont et al, ; Courade, Chassaing, Bardin, Alloui, & Eschalier, , Courade, Caussade, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The dissociative anesthetics ketamine induces analgesic effects in models of acute pain and relieves thermal and mechanical allodynia in a chronic neuropathic pain model [125]. The involvement of the serotonergic neurotransmission in analgesic actions has been studied using neuropathic pain models in rats [126]. The gender difference in pain sensation and emotional domain has been reported using the transgenic mouse model of Alzheimer's disease [127].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%